2019
DOI: 10.4236/health.2019.115048
|View full text |Cite
|
Sign up to set email alerts
|

Significant Differences in Elderly Health between Urban and Rural Communities: A Literature Review

Abstract: This study aimed to examine measures pertaining to elderly health in urban versus rural settings, and to identify differences in the health of elderly people living in urban and rural communities through a literature review. An electronic literature search was performed using PubMed for English articles published in peer-reviewed journals up to August 2018, with the following search terms: "urban", "rural", "comparison of community", "elderly health", and "comparison of community health". A total of 35 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This suggests that there is a tendency for healthcare services to be pro-intellectualized, given the generally low level of education in rural China. In rural areas, people with a good level of education have a more correct understanding of inpatient care, as well as preventive healthcare services, and can promote their use of these services (40). Firstly, there are significant urban-rural differences in the impact of formal support on the utilization of healthcare services for older people.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there is a tendency for healthcare services to be pro-intellectualized, given the generally low level of education in rural China. In rural areas, people with a good level of education have a more correct understanding of inpatient care, as well as preventive healthcare services, and can promote their use of these services (40). Firstly, there are significant urban-rural differences in the impact of formal support on the utilization of healthcare services for older people.…”
Section: Discussionmentioning
confidence: 99%
“…The result indicates that urban elderly were expected to lose healthy years of life due to short-term morbidity in comparison to rural counterparts. The role of rural-urban settings in determining the health status of the elderly is varied across studies [20]. Currently unmarried elderly were less likely to report short-term morbidity at the follow-up, and evidence for such an association is weak in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that focusing on differences in environment between rural and urban communities as one of the characteristics of residential community, social function and mental health or depression of elderly individuals might be more important as outcome measures of effective integrated communitybased care [3]. However, the outbreak of the coronavirus disease 19 (COVID-19) around 2020 has influenced the health and the daily life of residential people in a community through social distance.…”
Section: Introductionmentioning
confidence: 99%